Role of Sulfated Glycans in Adherence of the Microsporidian Encephalitozoon intestinalis to Host Cells In Vitro - Hayman, J. Russell (American Society for Microbiology, 2005)
Microsporidia are obligate intracellular opportunistic protists that infect a wide variety of animals, including humans, via environmentally resistant spores. Infection requires that spores be in close proximity to host cells so that the hollow polar tube can pierce the cell membrane and inject the spore contents into the cell cytoplasm. Like other eukaryotic microbes, microsporidia may use specific mechanisms for adherence in order to achieve target cell proximity and increase the likelihood of successful infection. Our data show that Encephalitozoon intestinalis exploits sulfated glycans such as the cell surface glycosaminoglycans (GAGs) in selection of and attachment to host cells. When exogenous sulfated glycans are used as inhibitors in spore adherence assays, E. intestinalis spore adherence is reduced by as much as 88%. However, there is no inhibition when nonsulfated glycans are used, suggesting that E. intestinalis spores utilize sulfated host cell glycans in adherence. These studies were confirmed by exposure of host cells to xylopyranoside, which limits host cell surface GAGs, and sodium chlorate, which decreases surface sulfation. Spore adherence studies with CHO mutant cell lines that are deficient in either surface GAGs or surface heparan sulfate also confirmed the necessity of sulfated glycans. Furthermore, when spore adherence is inhibited, host cell infection is reduced, indicating a direct association between spore adherence and infectivity. These data show that E. intestinalis specifically adheres to target cells by way of sulfated host cell surface GAGs and that this mechanism serves to enhance infectivity.